Responsabilidade civil por danos decorrentes da alienação parental - Dirscherl, Fernanda Pantaleão (2021)
The present thesis to discuss the civil liability by the parental alienation acts and the context of the respective duty to repair, verifying the implications of the legalpsychological consequences of parental alienation for the agents involved, making considerations about the respective configuration of civil responsibility not only under the strict perspective of Law but also of Psychology. For that, the deductive method was used, starting from the basic premise of the paradigm change of the family as an institution and getting at the specific premise of the interaction between the Tort Law and Family Law; and the dialogic method, through which an interdisciplinary and transdisciplinary dialogue was established, thus searching a study that involves basic and important knowledge from other areas of Law and also with an interface with Psychology. At the end, the types of damage involved in the practice of acts of parental alienation were understood, as well as the objective character of the civil liability of the alienator and the resulting duty, including not only the need to repair but also the resocialize.